Tuning of the acid sites in the zeolite-alumina composite Ni catalysts and their impact on the palm oil hydrodeoxygenation reaction - Dabbawala, Aasif A.; Al Maksoud, Walid; Abou-Hamad, Edy; Charisiou, Nikolaos D.; Constantinou, Achilleas; Harkou, Eleana; Latsiou, Angeliki I.; AlKhoori, Sara; Hinder, Steve J.; Baker, Mark A.; Anjum, Dalaver H.; Kobayashi, Yoji; et al. (My University, 2024)
The hydrodeoxygenation (HDO) of bio-oil is one of the potential approaches to produce green diesel. However, HDO catalyst requires the development of bifunctionality which translates to the simultaneous presence of acidic and metal sites for desired catalytic activity and selectivity. Zeolites and their composites are attractive candidates for the conversion of biomass to fuels. In the present work, a series of Ni-incorporated Al2O3-zeolite beta bifunctional composite catalysts with distinct Al2O3 (25–75 wt%) and Ni contents (5–15 wt%) were synthesized via a facile one-pot method directly from nickel acetate, nano-boehmite (γ-AlO(OH)) and the NH4+ form of beta zeolite (NH4+-BZ). The nano-boehmite particles, due to the positive charges on their surface, electrostatically attract negatively charged beta zeolite crystals, which leads to the assembly of a hierarchical pore structure upon calcination. Interestingly, the composite catalysts synthesized were quite homogeneous with uniform dispersion of Ni particles. All composite catalysts were thoroughly characterized using XRD, SEM-EDX, SEM-mapping, HR-TEM, H2-TPR, H2-TPD, NH3-TPD, XPS, 31P MAS NMR, 27Al MAS NMR and N2 sorption analysis. The synthesized composite catalysts with distinct Al2O3 contents showed diverse textural properties, distinct nature of acid sites and improved performance in hydrodeoxygenation of palm oil. Particularly, the Ni/BZ-Al50 (with BZ:Al2O3 = 50:50) composite catalyst significantly enhanced the conversion of palm oil (up to 90%) and yield of n-C15-C18 hydrocarbons (up to 69%) at moderate temperature of 375 °C as compared to 10Ni/BZ catalyst (Conv. = 75%, yield of n-C15-C18 = 52%). The higher catalytic performance realized with composite catalysts can be ascribed to its hierarchical pore structure, moderate acidity (chemisorption studies), tuned acid sites nature (solid state NMR) and homogeneous distribution of active Ni sites (H2 chemisorption) which helps to improve product selectivity by minimizing side reactions. The time-on-stream (TOS) experiments were carried out up to 20 h which clearly showed that composite catalysts are more stable suggesting the lower amount of coke deposition (TPO studies) and suppression of metal sintering.
Keywords: Acid sites; Hydrodeoxygenation; Nickel, bifunctional catalyst; Palm oil; Selective deoxygenation; Solid state NMR